Mechanisms of substrate recognition by a typhoid toxin secretion-associated muramidase - Geiger, Tobias; Lara-Tejero, Maria; Xiong, Yong; Galán, Jorge E (eLife, 2020)
Typhoid toxin is a virulence factor for the bacterial pathogen Salmonella Typhi, which causes typhoid fever in humans. After its synthesis by intracellular bacteria, typhoid toxin is secreted into the lumen of the Salmonella-containing vacuole by a secretion mechanism strictly dependent on TtsA, a specific muramidase that facilitates toxin transport through the peptidoglycan layer. Here we show that substrate recognition by TtsA depends on a discrete domain within its carboxy terminus, which targets the enzyme to the bacterial poles to recognize YcbB-edited peptidoglycan. Comparison of the atomic structures of TtsA bound to its substrate and that of a close homolog with different specificity identified specific determinants involved in substrate recognition. Combined with structure-guided mutagenesis and in vitro and in vivo crosslinking experiments, this study provides an unprecedented view of the mechanisms by which a muramidase recognizes its peptidoglycan substrate to facilitate protein secretion.
Keywords: protein secretion; muramidase; peptidoglycan remodeling; bacterial envelope; L-D transpeptidase